(Phenylamino)pyrimidine-1,2,3-triazole derivatives as analogs of imatinib: searching for novel compounds against chronic myeloid leukemia - Pimentel, Luiz Claudio Ferreira; Hoelz, Lucas Villas Boas; Canzian, Henayle Fernandes; Branco, Frederico Silva Castelo; de Oliveira, Andressa Paula; Campos, Vinicius Rangel; Júnior, Floriano Paes Silva; Dantas, Rafael Ferreira; Resende, Jackson Antônio Lamounier Camargos; Cunha, Anna Claudia; Boechat, Nubia; Bastos, Mônica Macedo (Beilstein Journal of Organic Chemistry, 2021)
The enzyme tyrosine kinase BCR-Abl-1 is the main molecular target in the treatment of chronic myeloid leukemia and can be competitively inhibited by tyrosine kinase inhibitors such as imatinib. New potential competitive inhibitors were synthesized using the (phenylamino)pyrimidine-pyridine (PAPP) group as a pharmacophoric fragment, and these compounds were biologically evaluated. The synthesis of twelve new compounds was performed in three steps and assisted by microwave irradiation in a 1,3-dipolar cycloaddition to obtain 1,2,3-triazole derivatives substituted on carbon C-4 of the triazole nucleus. All compounds were evaluated for their inhibitory activities against a chronic myeloid leukemia cell line (K562) that expresses the enzyme tyrosine kinase BCR-Abl-1 and against healthy cells (WSS-1) to observe their selectivity. Three compounds showed promising results, with IC50 values between 1.0 and 7.3 μM, and were subjected to molecular docking studies. The results suggest that such compounds can interact at the same binding site as imatinib, probably sharing a competitive inhibition mechanism. One compound showed the greatest interaction affinity for BCR-Abl-1 in the docking studies.
Keywords: chronic myeloid leukemia; 1,3-dipolar cycloaddition; imatinib; (phenylamino)pyrimidine-pyridine; 1,2,3-triazole

(untitled) - Geary, C. G. (Br. J. Haematol., 2000)

(untitled) - de Azevedo, L. D.; Bastos, M. M.; de Oliveira, A. P.; Boechat, N. (Quim. Nova, 2017)

(untitled) - Burmeister, T.; Schwartz, S.; Bartram, C. R.; Gökbuget, N.; Hoelzer, D.; Thiel, E. (Blood, 2008)

(untitled) - Jabbour, E.; Kantarjian, H. (Am. J. Hematol., 2018)

(untitled) - Yaish, P.; Gazit, A.; Gilon, C.; Levitzki, A. (Science, 1988)

(untitled) - Zhang, Q.; Zhang, X.; You, Q. (Molecules, 2016)

(untitled) - Rossari, F.; Minutolo, F.; Orciuolo, E. (J. Hematol. Oncol., 2018)

(untitled) - Rodriguez, M.; Cardona, A. F.; Grajales, M. A.; Enciso, L.; Ruiz, G.; Yepes, A.; Ospina, V.; Gálvez, K.; García, J.; Rosales, J.; Rosales, M.; Quintero, G.; et al. (Rev. Venez. Oncol., 2007)

(untitled) - Kannaiyan, R.; Mahadevan, D. (Expert Rev. Anticancer Ther., 2018)

(untitled) - Alves, R. d. C. S. (Rev. Bras. Hematol. Hemoter., 2009)

(untitled) - Hochhaus, A.; Larson, R. A.; Guilhot, F.; Radich, J. P.; Branford, S.; Hughes, T. P.; Baccarani, M.; Deininger, M. W.; Cervantes, F.; Fujihara, S.; Ortmann, C.-E.; Menssen, H. D.; et al. (N. Engl. J. Med., 2017)

WO Patent - Boechat, N. A.; Bastos, M. M.; Maia, R. C. (Phenylaminopyrimidine-derived compounds, method for producing the same, use of said compounds for the treatment of cancer, and treatment methods, 2016)

(untitled) - Azevedo, L. D.; Bastos, M. M.; Vasconcelos, F. C.; Hoelz, L. V. B.; Junior, F. P. S.; Dantas, R. F.; de Almeida, A. C. M.; de Oliveira, A. P.; Gomes, L. C.; Maia, R. C.; Boechat, N. (Med. Chem. Res., 2017)

(untitled) - Nath, P. S.; Ashish, P.; Rupesh, M. (Int. J. Res. Ayurveda Pharm., 2011)

(untitled) - Huisgen, R. (Proc. Chem. Soc., London, 1961)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Dheer, D.; Singh, V.; Shankar, R. (Bioorg. Chem., 2017)

(untitled) - Bozorov, K.; Zhao, J.; Aisa, H. A. (Bioorg. Med. Chem., 2019)

(untitled) - Kharb, R.; Sharma, P. C.; Yar, M. S. (J. Enzyme Inhib. Med. Chem., 2011)

(untitled) - Kaur, P.; Kaur, R.; Goswami, M. (Int. Res. J. Pharm., 2018)

(untitled) - Zhou, C.-H.; Wang, Y. (Curr. Med. Chem., 2012)

(untitled) - Bonandi, E.; Christodoulou, M. S.; Fumagalli, G.; Perdicchia, D.; Rastelli, G.; Passarella, D. (Drug Discovery Today, 2017)

(untitled) - Banerji, B.; Chandrasekhar, K.; Sreenath, K.; Roy, S.; Nag, S.; Saha, K. D. (ACS Omega, 2018)

(untitled) - Yuan, M.; Huang, L.-L.; Chen, J.-H.; Wu, J.; Xu, Q. (Signal Transduction Targeted Ther., 2019)

(untitled) - Arioli, F.; Borrelli, S.; Colombo, F.; Falchi, F.; Filippi, I.; Crespan, E.; Naldini, A.; Scalia, G.; Silvani, A.; Maga, G.; Carraro, F.; Botta, M.; et al. (ChemMedChem, 2011)

(untitled) - Li, Y.-T.; Wang, J.-H.; Pan, C.-W.; Meng, F.-F.; Chu, X.-Q.; Ding, Y.-h.; Qu, W.-Z.; Li, H.-y.; Yang, C.; Zhang, Q.; Bai, C.-G.; Chen, Y. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Kalesh, K. A.; Liu, K.; Yao, S. Q. (Org. Biomol. Chem., 2009)

(untitled) - Boechat, N.; Bastos, M. M.; Duarte, S. L.; Costa, J. C. S.; Mafra, J. C. M.; Daniel, L. C. C. (Rev. Virtual Quim., 2013)

Repub. Korean Pat. Appl. - Yeon, K. D.; Jim, C. D.; Yeol, L. G.; Yeop, K. H.; Hun, W. S.; Fon, L. H.; Mu, K. S.; Am, C. (N-Phenyl-2-pyrimidine isothiocyanate derivatives and preparation process thereof, 2012)

(untitled) - Moorhouse, A. D.; Moses, J. E. (Synlett, 2008)

(untitled) - Tetko, I. V.; Tanchuk, V. Y. (J. Chem. Inf. Comput. Sci., 2002)

(untitled) - Xie, T.; Saleh, T.; Rossi, P.; Kalodimos, C. G. (Science, 2020)

(untitled) - Singh, K.; Gangrade, A.; Jana, A.; Mandal, B. B.; Das, N. (ACS Omega, 2019)

(untitled) - Badisa, R. B.; Darling-reed, S. F.; Joseph, P.; Cooperwood, J. S.; Latinwo, L. M.; Goodman, C. B. (Anticancer Res., 2009)

(untitled) - Saftić, D.; Žinić, B.; Glavaš-Obrovac, L.; Studzińska, M.; Paradowska, E.; Leśnikowski, Z. J. (Nucleosides, Nucleotides Nucleic Acids, 2018)

(untitled) - Yang, J.; Campobasso, N.; Biju, M. P.; Fisher, K.; Pan, X.-Q.; Cottom, J.; Galbraith, S.; Ho, T.; Zhang, H.; Hong, X.; Ward, P.; Hofmann, G.; et al. (Chem. Biol., 2011)

(untitled) - Azam, M.; Seeliger, M. A.; Gray, N. S.; Kuriyan, J.; Daley, G. Q. (Nat. Struct. Mol. Biol., 2008)

(untitled) - Roskoski, R., Jr (Pharmacol. Res., 2019)

BRUKER APEX2, v2014.5-0 (Bruker AXS Inc., 2007)

SAINT, V8.34A (Bruker AXS Inc., 2013)

SADABS: Program for Empirical Absorption Correction of Area Detector Data (University of Göttingen, 1996)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Adv., 2015)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)

(untitled) - Macrae, C. F.; Edgington, P. R.; McCabe, P.; Pidcock, E.; Shields, G. P.; Taylor, R.; Towler, M.; van de Streek, J. (J. Appl. Crystallogr., 2006)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)

(untitled) - Meng, X.; Li, M.; Wang, X.; Wang, Y.; Ma, D. (Cancer Sci., 2009)

(untitled) - de Beaufort, A. J.; Bakker, A. C.; van Tol, M. J. D.; Poorthuis, B. J.; Schrama, A. J.; Berger, H. M. (Pediatr. Res., 2003)

(untitled) - Thomsen, R.; Christensen, M. H. (J. Med. Chem., 2006)

(untitled) - Wagner, J. R.; Churas, C. P.; Liu, S.; Swift, R. V.; Chiu, M.; Shao, C.; Feher, V. A.; Burley, S. K.; Gilson, M. K.; Amaro, R. E. (Structure, 2019)